Risk Factors of Rebound Hyperbilirubinemia in Post Phototherapy Hyperbilirubinemia Infants - Alexander Leonard Caesar Josediputra; Martono Tri Utomo; Risa Etika (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Post phototherapy rebound hyperbilirubinemia is a cause for readmission in some infants.However, this phenomenon data of rebound hyperbilirubinemia is lacking from Indonesia. Our study aimsto describe the risk factor of post phototherapy rebound hyperbilirubinemia in the infant.Method: Cross-sectional study of all infants with indirect hyperbilirubinemia who were treated phototherapyaccording to standard guidelines in neonate intermediate unit Dr. Soetomo hospital for 6 months from June2017 until December 2017. Bilirubin was measured 24 hours after phototherapy. Bilirubin rebound isconsidered as increasing total serum bilirubin that needs reinstitution of phototherapy.Result: A total of 53 (44.9%) infants developed rebound hyperbilirubinemia. We revealed the following riskfactor for rebound hyperbilirubinemia was the onset of jaundice on < 3 days, (10 babies, p <0.05). Otherresults are 30 (56.6%) female infants, 39 (73%) birth weight < 2500 g, 36 (67%) infants with a history ofcesarean section, and 38 (71%) preterm infants but there are not statistically significant.Conclusion: Post phototherapy rebound hyperbilirubinemia should be considered in the onset of jaundice< 3 days.